1999
DOI: 10.1302/0301-620x.81b1.0810155
|View full text |Cite
|
Sign up to set email alerts
|

Induction of macrophage C-C chemokine expression by titanium alloy and bone cement particles

Abstract: Particulate wear debris is associated with periprosthetic inflammation and loosening in total joint arthroplasty. We tested the effects of titanium alloy (Ti-alloy) and PMMA particles on monocyte/macrophage expression of the C-C chemokines, monocyte chemoattractant protein-1 (MCP-1), monocyte inflammatory protein-1 alpha (MIP-1␣), and regulated upon activation normal T expressed and secreted protein (RANTES). Periprosthetic granulomatous tissue was analysed for expression of macrophage chemokines by immunohist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
99
1
2

Year Published

1999
1999
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(110 citation statements)
references
References 30 publications
8
99
1
2
Order By: Relevance
“…MCP-1 and MIP-I alpha are found in membranes retrieved from failed TJA [27]. In vitro analysis has identified macrophages exposed to particulate debris as one possible source of MCP-1 and MIP-1 alpha [17,27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MCP-1 and MIP-I alpha are found in membranes retrieved from failed TJA [27]. In vitro analysis has identified macrophages exposed to particulate debris as one possible source of MCP-1 and MIP-1 alpha [17,27].…”
Section: Introductionmentioning
confidence: 99%
“…In vitro analysis has identified macrophages exposed to particulate debris as one possible source of MCP-1 and MIP-1 alpha [17,27]. However, the effect of particles on fibroblast release of macropliage chemoattractant factors remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have also shown a variety of cell signaling pathways are involved in the cellular response to debris. These include mitogenactivated protein kinase activation [1], induction of granulocyte macrophage colony-stimulating factor [6], C-C chemokine expression [55], matrix metalloproteinase induction [56], NFkB activation [59,66,72], nitric oxide elicitation [45,64,75], induction of apoptosis [74], cytokine activation [43,78], and direct activation of cyclooxygenase-2 [82]. Although most studies on the etiology of aseptic loosening have been focused on macrophage as the central cell of interest, there is recent interest in examining the role of the fibroblasts in the MMPs 56 UHMWPE = ultrahigh-molecular-weight polyethylene; IL = interleukin; TNF = tumor necrosis factor; GM-CSF = granulocyte macrophage colony-stimulating factor; MMPs = matrix metalloproteinases.…”
Section: Search Strategy and Criteriamentioning
confidence: 99%
“…While several in vitro studies have examined the role of monocyte chemotactic protein 1 (MCP-1) in the synovial tissues of patients with chronic wear debris-induced inflammation [6,7,11,19,24,36], none assessed MCP-1 in synovial fluid of patients undergoing TKA revision surgery for aseptic loosening. Collectively, these in vitro studies demonstrate increased MCP-1 gene expression and protein associated with chronic wear debris.…”
Section: Introductionmentioning
confidence: 99%
“…Collectively, these in vitro studies demonstrate increased MCP-1 gene expression and protein associated with chronic wear debris. These studies focused on titanium [6,7] and polymethylmethacrylate particles [24]. Fritz et al [6,7] performed analyses with human bone marrow-derived and osteosarcoma cells.…”
Section: Introductionmentioning
confidence: 99%